Investigation of the Common Mode Voltage for a Neutral-Point-Clamped Multilevel Inverter Drive and its Innovative Elimination through SVPWM Switching-State Redundancy - C. Bharatiraja; J.L. Munda; N. Sriramsai; T Sai Navaneesh (Institute of Advanced Engineering and Science, 2016)
The purpose of this paper is to provide a comprehensive Investigations and its control on the common mode Voltage (CMV) of the three-phase three-level neutral-point diode-clamped (NPC) multilevel inverter (MLI). A widespread space-vector pulse width modulation (SVPWM) technique to mitigate the perpetual problem of the NPC-MLI, the CMV, proposed. The proposed scheme is an effectual blend of nearest three vector (NTV) and selected three vector (STV) techniques. This scheme is capable to reduce the CMV without compromise the inverter output voltage and Total harmonics distraction (THD). CMV reduction achieved less than +Vdc/6 using the proposed vector selection procedure. The theoretical Investigations, the MATLAB software based computer simulation and Field Programmable Gate Array (FPGA) supported hardware corroboration have shown the superiority of the proposed technique over the conventional SVPWM schemes.